Improvement of the Youth Social Integration - Kučinskienė, Ramutė; Kučinskas, Vytolis (Acta Paedagogica Vilnensia, 2002)
The problems of socialization and social integration of the contemporary young generation are analysed in the article. Insufficient learning motivation, dissatisfaction in current school life and refusing to go to school, inability to make rational plans for future (learning, career, family, etc.), finding ways how to realize them, and finding ways of socially acceptable living are the topics which are of high importance in many modern countries and in Lithuania too. The aim of the research was to enclose the main methodological premises enabling to optimize current development of human resources in many societies of today. The role of the educational system in the process of socialization is under discussion: could it be in action in future as before, and if the answer is "yes", how it should be developed for more efficient performance? It is decided that we do not have enough personal and social courage and methods for creation of absolutely new system of education up to now. In such case we discuss only about some innovative ways of thinking and restructuring of the existing educational system. The main conclusions of the presented research are the following: permanent changes in societies call for making new goals and content of the socialization process. The countries under political, economical, cultural and educational transition (as Lithuania is) must find new ways creating closer social cooperation between local, national and global levels and different institutions of education. The system of education should be integrated with the social partners and society's institutions in much more extent. Closer ties should be developed among basic education and vocational education, and school, family, local community and the world of work are expected to form new and more efficient connections. Making new strategies for young generation socialization knowledge of various social and humanitarian sciences should be united in much more extent than it used to be, and contribution of economists and politicians is necessary. There is clear need for youth’s socialization research and creating of new social structures based on systematic approach in Lithuania. Forms of international cooperation in establishing new models of youth social mobility and employment are mentioned as potentially productive also.
Keywords: Education system; youth; socialization; social integration; social life